Honduras: IFAD Technical Assistance Grant, 1997-98 - International Food Policy Research Institute (International Food Policy Research Institute, 2000)
The dataset focuses on household food and nutrition security in western Honduras. The questionnaires were administered to 4,810 individuals in 691 households from 39 communities in four rounds from March, 1997, through April, 1998. Two-thirds of the households surveyed either received or were expected to receive services from an IFAD-funded rural development project. The other one-third were matched control communities. Topics include general household and household member characteristics; employment and sources of off-farm income; access to land; on-farm production; use and post-harvest losses of farm produce; production of key crops; household assets; credit and transfers in; participation in organized groups; schooling and literacy; housing conditions; coping strategies; anthopometry of children under five years; and diet, feeding, mordibity, and hunger.